Glycosphingolipids and their impact on platelet activity in a murine model of fabry disease - Adam J. Kanack; Eve Prodoehl; Mayumi Ishihara-Aoki; Kazuhiro Aoki; Nancy M. Dahms (Scientific Reports)
Abstract Fabry disease is an X-linked lysosomal storage disorder caused by deficiency of the lysosomal enzyme ⍺-galactosidase-A (⍺-Gal A), resulting in widespread accumulation of terminal galactose-containing glycosphingolipids (GSLs) and the impairment of multiple organ systems. Thrombotic events are common in Fabry patients, with strokes and heart attacks being significant contributors to a shortened lifespan in patients of both genders. Previously, we developed an ⍺-Gal A-knockout (KO) murine model that recapitulates most Fabry symptomologies and demonstrated that platelets from KO males become sensitized to agonist-mediated activation. In the current report, we used mass spectrometry, platelet-based assays and histology to define further the mechanisms linking GSL accumulation with thrombotic phenotypes in both sexes. Sera and platelets from ⍺-Gal A-KO females have elevated levels of Fabry-associated GSLs relative to wild-type females, but accumulated less of these GSLs than KO males. Correspondingly, KO females demonstrate a less severe thrombotic phenotypes than KO males. Notably, treatment of platelets from wild-type animals with globotriaosylceramide (Gb3) increased baseline platelet activation and aggregation. In contrast, several control GSLs did not stimulate platelet responses. These data suggest that chronically high concentrations of the Fabry-associated GSL, Gb3, contributes to the prothrombotic phenotypes experienced by Fabry patients by directly stimulating platelet activation.